2018
DOI: 10.2109/jcersj2.17247
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the orthorhombic phase in (111)-oriented YO<sub>1.5</sub>-substituted HfO<sub>2</sub> films

Abstract: Ferrolectric orthorhombic HfO 2-based films are potential candidates for future ferroelectirc applications. The stability of the orthorhombic phase of epitaxial YO 1.5-substituted HfO 2 films on (111) yttria-stabilized zirconia substrates was investigated for various compositions, thicknesses and underlying layers. In the case of 14 nmthick films, only 7 mol % film consisted of a single orthrohombic phase. With decreasing amount of YO 1.5 or increasing thickness, the paraelectric monoclinic phase formed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…These XRD 2D maps were beneficial for the phase identifications described elsewhere. 18,19) It is confirmed from Ψ angles where the 110 diffraction peaks located that both the YHO-7 films deposited with and without O 2 mainly consist of the orthorhombic phase, as discussed in a previous study. 19) The crystal structure characterization based on XRD measurements revealed a small difference between the films without and with O 2 during sputtering deposition in this study.…”
Section: Effect Of the Atmosphere During Depositionsupporting
confidence: 75%
See 1 more Smart Citation
“…These XRD 2D maps were beneficial for the phase identifications described elsewhere. 18,19) It is confirmed from Ψ angles where the 110 diffraction peaks located that both the YHO-7 films deposited with and without O 2 mainly consist of the orthorhombic phase, as discussed in a previous study. 19) The crystal structure characterization based on XRD measurements revealed a small difference between the films without and with O 2 during sputtering deposition in this study.…”
Section: Effect Of the Atmosphere During Depositionsupporting
confidence: 75%
“…X-ray diffraction (XRD) measurement was performed by the standard θ-2θ method (Philips X'Pert-MRD). 18,19) To confirm the crystal symmetry of the films, further XRD measurement for two-dimensional (2D) reciprocal space mappings (RSMs) was performed using a diffractometer (Bruker D8 DISCOVER) and a 2D detector (Bruker VÅNTEC-500). 100-nm-thick Pt circular top electrodes 50 µm in diameter were deposited by electron beam evaporation through a metal mask at room temperature.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Shimizu et al reported the growth of epitaxial YO 1.5 -doped HfO 2 films with various Y concentrations between 5% and 9% on (100)­YSZ and (111)­YSZ substrates, which have good lattice matching with these films. These structural analyses revealed that 5%, 6%, and 7%YO 1.5 -doped HfO 2 thin films consist mainly of an orthorhombic phase, while 8% and 9%YO 1.5 -doped HfO 2 thin films consist of a major tetragonal phase together with a small amount of the orthorhombic phase. This result suggests that the constituent phase can be controlled by adjusting the Y doping concentration in the HfO 2 thin film.…”
Section: Introductionmentioning
confidence: 99%
“…32,34,35) On the other hand, there were three possible domains in the (111)-Y-HfO 2 film, and all of them could contribute to the remnant polarization. 36) Therefore, the larger remnant polarization in the (111)-Y-HfO 2 film can be partially attributed to its domain structure, although other factors, such as leakage current and imperfect poling, may also affect the measured remnant polarization.…”
Section: Methodsmentioning
confidence: 99%
“…29) Thereafter, several studies were conducted on not only polycrystalline but also epitaxial ferroelectric HfO 2 -based films with various compositions, and their ferroelectricity is stable over a wide range of film thicknesses, usually less than 100 nm. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] The thickness scalability of ferroelectric polarization was recently reported by Shimura et al and Mimura et al They reported that epitaxial and polycrystalline Y-doped HfO 2 (Y-HfO 2 ) films fabricated on yttria-stabilized zirconia (YSZ) and platinized (001) Si at room temperature by radiofrequency (RF) magnetron sputtering and pulsed laser deposition showed stable ferroelectricity regardless of their thickness and orientation. [38][39][40][41] HfO 2 -based materials have been integrated as high-k gate insulators compatible with the Si-based complementary metal-oxide-semiconductor (CMOS) process.…”
Section: Introductionmentioning
confidence: 94%